(3QSGdI aj RjGOGJ Ydi cJGH GdeYWjGJ dChbdjOSs - (3CHh Sgd hjLf Hf QSJe Gdchgi (B( (3Gdbhgi (B)s; (3GhbdjOSs ((3OeTb s)
(3ChdgG (B:s
(3EPG cGfJ ebGOjQ hcGfJ fSHI cd hGMO efgG Edi BNQ eYdheg aEf fSHI LejYgG Edi Pdc GdebOGQ eYdheI s
(3BNQgG (B:s
(3hEeG Gf jchf GMOgeG GYXe ef ebOGQ fSHJg Edi GdBNQ eYdheI HTF eYdhe hPdc eG CQOfG Gf fHjf JeJ GdCTcGd GdJi RGOgG CHh Sgd Gdchgj ai cJGH GdeYWjGJ dChbdjOS hgj (B35 (3TcdkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3jTJed Ydi CTcGd gfOSjI s
(3HBNQgG eWGdYI deMeO Hf SQjGb GdeQGYis
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdQjGVjGJs